Análise da usabilidade do portal da Universidade Federal do Piaui-UFPI como serviço de governo eletrônico - Barbosa, Albenir Rêgo (2018)
Electronic Government has emerged with the aim of providing greater integration between government, citizens and organizations through the dissemination of new Information and Communication Technologies (ICTs). Faced with this, the online portals of different public institutions have emerged to meet the communication needs between Public Administration and society and to provide adequate and timely information to users of public services. The online portals of the public institutions are e-services that can have their performance evaluated in order to allow their improvement. In this context, including an entity of the Indirect Federal Public Administration, the unit of analysis to define the study environment was defined. This unit of analysis refers to the Federal University of Piauí-UFPI online portal. In this way, the objective of this dissertation is: To evaluate the online portal of the Federal University of Piauí-UFPI in light of the usability benchmarks proposed by Baker (2009). Specifically, the objective is: (i) to qualitatively characterize the use of the online portal of the Federal University of Piauí-UFPI in the six dimensions of analysis proposed by Baker (2009); (ii) to size the usability of the online portal of the Federal University of Piauí-UFPI; and (iii) compose the usability index of the online portal of the Federal University of Piauí-UFPI based on Baker's methodological framework (2009). The research does content analysis in a holistic case study. The objectives are descriptive and have a qualitative nature with a mixed approach of the data. The data treatment and analysis were submitted to documentary analysis and descriptive statistics. The results evidenced that Electronic Government is an identified way in the contemporary Public Administration for the provision of public services to content. The analysis of the UFPI online portal in the six dimensions of the Baker methodological framework (2009) allowed to identify a usability index with 59.71 weighted points and 54 gross points. It is inferred, therefore, that the online portal of the UFPI has good usability and does not block its users to adequate access in its process of improvement as an Electronic Government service.